Organizational Justice Among Private University Lecturers in Riau, Indonesia - Arrafiqur Rahman; Norhayah Zulkifli; Adolf Bastian; Gilang Nugroho; Andi Afrizal (Lembaga Publikasi Ilmiah Nusantara, 2026)
Organizational justice, defined as employees’ perceptions of fairness in institutional outcomes, procedures, and interpersonal treatment, is a crucial issue in human resource management, particularly in higher education. While this construct has been widely examined in Western corporate and healthcare contexts, empirical evidence from private higher education institutions in developing economies remains limited and inconsistent. Indonesian private university lecturers have received little scholarly attention, despite ongoing welfare and governance challenges. Addressing this gap, this study investigates lecturers’ perceptions of organizational justice in private universities in Riau Province, Indonesia. Using a quantitative survey design with proportional stratified random sampling, data were collected from 298 lecturers across seven private universities. The research instrument, adapted from Colquitt and Zipay (2015), measured three dimensions of organizational justice: distributive, procedural, and interactional justice, through 20 items on a five-point Likert scale. Descriptive statistical analysis was employed to calculate achievement scores for each item and dimension. The findings show a mean organizational justice score of 3.167, with an achievement level of 63.35%, indicating that lecturers perceive institutional fairness as moderately adequate. The highest frequency appeared in the 56–64 interval class, suggesting a generally moderate perception of justice. These results indicate the need for private universities in Riau to strengthen fairness in reward distribution, decision-making procedures, and interpersonal treatment. This study contributes an empirical baseline for organizational justice among lecturers in a resource-constrained Indonesian higher education context and offers practical insights for governance reform and human resource policy development.